Three phase inverter development using common mode voltage pulse width modulation (PWM) method - Abd Halim, Hasmizar (2013)
This master report presents a simulation voltage source control system for three phase inverter focusing on reducing the common mode voltage using diode clamped circuit. The model was implemented using MATLAB-Simulink with the SimPowerSystems Block set and also M-file. The twelve Insulated Gate Bipolar Transistor (IGBTs) was use as a switching device. In the three phase inverter circuit, an Alternating Current (AC) output is synthesized from a Direct Current (DC) input by closing and opening the switches in correct sequence or switching system. The Pulse Width Modulation (PWM) is a program in M-file to control the ON/OFF switching scheme of the IGBTs. An output voltage of an inverter with diode clamped before load and after load will be monitored, discussed and compared to the basic three phase inverter. This inverter circuit operate in open loop system where the inverter output and the load in series connection. The effectiveness of the method will be compared with the basic three phase inverter simulation model in MATLABSimulink program.